ANALISIS FAKTOR PENYEBAB KESULITAN MEMBACA PERMULAAN PADA PESERTA DIDIK KELAS I DI MIM BULAK KRAGAN KARANGANYAR TAHUN PELAJARAN 2021/2022 - Susilowati, Nevi; Hartini, Sri; Sarafuddin, Sarafuddin (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
Thle purlpose of thlis studly was to describe the factorls thalt causle students to experience difficulty in beginning reading, to find out tlhe tealcher's strategy iln overlcoming initial reading difficullties, and to find out the results of the analysis of initial reading difficulties in class I students. The research method is descriptive qualitative. The subjects used were 5 class I students, parents, and class teachers. The object of this study was the difficulty factor for beginning reading in class I students. The data sources obtained were primary data and secondary data. Data collection techniques are observation, interviews, and documentation. The data validation technique uses source triangulation and technique triangulation. With data analysis: Data reduction, Data presentation, and Data verification. Based on the data analysis, it can be concluded that, (1) there are internal and external factors that affect the difficulty of beginning reading, (2) the teacher uses a strategy by giving special guidance and a personal approach to students. (3) There were 5 students who had difficulty reading at the beginning and these difficulties varied.